Optimization Of Online Learning: Implementation Of E-Learning Models In Islamic Education Programs - Abdul Qodir; Eneng Muslihah; Ridwan Setiawan (Institut Agama Islam An-Nawawi Purworejo, 2024)
This article examines how learning is implemented in higher education, in implementing online learning models, especially in the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, Sultan Maulana Hasanuddin State Islamic University, Banten because the implementation of learning models is one of the main factors in the learning process. This research aims to determine the effectiveness of the online learning model in the Islamic Religious Education study program, Faculty of Tarbiyah and Teacher Training, Sultan Maulana Hasanuddin State Islamic University, Banten. The research method used uses a qualitative method with a descriptive type. Based on data analysis, it was found that the online learning model in the Islamic Religious Education study program, Tarbiyah and Teacher Training Faculty, Sultan Maulana Hasanuddin State Islamic University, Banten is divided into eight platforms. Meanwhile, regarding the effectiveness of the online learning model which has proven to be very effective because students experience online learning directly by lecturers and lecturers apply online learning with various platforms with professionals in front of students even though there are inhibiting and supporting factors which act as encouragement so that these activities can run in accordance with what is expected and desired.